2009
DOI: 10.1002/adem.200800367
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Ultrastructure with Mechanical Properties of Nano‐Hybrid Dental Composites

Abstract: Determination of mechanical properties of nano‐hybrid dental composites leads to strong correlation to material's ultrastructure. Not only does total filler content in percentage of weight affect the mechanical properties, but the combination of optimal filler size and shape with homogeneous distribution of filler particles and an optimal amount of different sized fillers in finally cured dental composites lead to desired mechanical and thermo‐mechanical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…A comprehensive overview was published by Ramakrishna and coauthors in 2001 [ 248 ]. In a recent publication the impact of the particle size, distribution, and geometrical shape on the resulting mechanical properties of different composites suitable as dental filling materials for substituting amalgams was summarized [ 249 ]. The authors found, that especially the homogenous nanoparticle distribution in the matrix ensured a long dental filler lifetime.…”
Section: Functional Properties and Applications Of Nanocompositesmentioning
confidence: 99%
“…A comprehensive overview was published by Ramakrishna and coauthors in 2001 [ 248 ]. In a recent publication the impact of the particle size, distribution, and geometrical shape on the resulting mechanical properties of different composites suitable as dental filling materials for substituting amalgams was summarized [ 249 ]. The authors found, that especially the homogenous nanoparticle distribution in the matrix ensured a long dental filler lifetime.…”
Section: Functional Properties and Applications Of Nanocompositesmentioning
confidence: 99%